Magneto‐Optical Sensing Beyond the Shot Noise Limit. Issue 1 (12th November 2021) - Pai, Yun‐Yi; Marvinney, Claire E.; Hua, Chengyun; Pooser, Raphael C.; Lawrie, Benjamin J.
Abstract: Magneto‐optical sensors including spin noise spectroscopies and magneto‐optical Kerr effect microscopies are now ubiquitous tools for materials characterization that can provide new understanding of spin dynamics, hyperfine interactions, spin‐orbit interactions, and charge‐carrier g‐factors. Both interferometric and intensity‐difference measurements can provide photon‐shot‐noise‐limited sensitivity, but further improvements in sensitivity with classical resources require either increased laser power that can induce unwanted heating and electronic perturbations or increased measurement times that can obscure out‐of‐equilibrium dynamics and slow experimental throughput. Proof‐of‐principle measurements have already demonstrated quantum enhanced spin noise measurements with a squeezed readout field that are likely to be critical to the nonperturbative characterization of spin excitations in quantum materials that emerge at low temperatures. Here, a truncated nonlinear interferometric readout for low‐temperature magneto‐optical Kerr effect and related magneto‐optical microscopies that is accessible with today's quantum optical resources is proposed. 10 nrad / Hz sensitivity is achievable with optical power as small as 1 µW. As a result, measurements may be performed at temperatures as low as 83 mK in commercially available dilution refrigerators. This combination of high sensitivity and low operating temperature is impossible to achieve with any classical measurement. The quantum advantage for the proposed measurements persists even in the limit of large loss and small squeezing parameters. Abstract : Classical magneto‐optical microscopies are workhorse tools for material characterization, but they are fundamentally limited in sensitivity by the photon shot noise limit. Here, the authors describe quantum enhanced magneto‐optical Kerr effect measurements that are accessible with today's quantum optical resources. This approach to quantum sensing of quantum materials enables 10 nrad / Hz sensitivity at temperatures well below 100 mK.